Prevalence, risk factors and associated ocular diseases of cerebral stroke: the population-based Beijing Eye Study - Jost B Jonas; Ya Xing Wang; Liang Xu; Wen Bin Wei (BMJ Open)
Objective To assess the prevalence of cerebral stroke in the general population of Beijing and its association with systemic risk factors and ocular diseases.Setting The population-based Beijing Eye Study was conducted in a rural and urban region of Beijing.Participants With eligibility criteria of age 50+ years and living in the study regions, 3468 subjects (78.8%) out of 4403 eligible individuals participated.Primary and secondary outcome measures The study participants underwent a detailed systemic and ophthalmological examination and an interview in which the occurrence of a previous stroke was assessed.Results A previous stroke was reported by 235 individuals (7.33%; 95% CI 6.43% to 8.24%). The prevalence of previous stroke increased from 2.0% (95% CI 0.9% to 3.1%) in the age group of 50 to <55 years to 21.9% (95% CI 16.4% to 27.4%) in the age group of 80+ years. In multivariable regression analysis, a higher prevalence of previous stroke was correlated (Nagelkerke R2=0.20) with the systemic parameters of older age (p<0.001; OR 1.06; 95% CI 1.04 to 1.08), male gender (p<0.001; OR 0.54; 95% CI 0.40 to 0.74), lower quality of life score (p<0.001; OR 1.39; 95% CI 1.25 to 1.55), higher prevalence of arterial hypertension (p<0.001; OR 2.86; 95% CI 2.05 to 3.98), and cardiovascular disease (p<0.001; OR 1.8554; 95% CI 1.34 to 2.56), and with the ocular parameter of higher prevalence of diabetic retinopathy (p<0.001; OR 4.41; 95% CI 2.38 to 8.18) or alternatively, with higher stage of diabetic retinopathy (p<0.001; OR 1.64; 95% CI 1.26 to 2.14).Conclusions In this North Chinese population aged 50+ years, the prevalence of a previous stroke was 7.33% (95% CI 6.43% to 8.24%). After adjusting for systemic risk factors of older age, male gender and higher prevalence of arterial hypertension and cardiovascular disease, a higher prevalence of a previous stroke was significantly correlated with a higher prevalence and stage of diabetic retinopathy. The prevalence of a previous stroke increased for each step of an increase in the stage of diabetic retinopathy with an OR of 1.64 (95% CI 1.26 to 2.14), and it increased by the presence of diabetic retinopathy with an OR of 4.41 (95% CI 2.38 to 8.18).